2013
DOI: 10.1073/pnas.1318596110
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity olfactory receptor for the death-associated odor cadaverine

Abstract: Carrion smell is strongly repugnant to humans and triggers distinct innate behaviors in many other species. This smell is mainly carried by two small aliphatic diamines, putrescine and cadaverine, which are generated by bacterial decarboxylation of the basic amino acids ornithine and lysine. Depending on the species, these diamines may also serve as feeding attractants, oviposition attractants, or social cues. Behavioral responses to diamines have not been investigated in zebrafish, a powerful model system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
235
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(248 citation statements)
references
References 36 publications
12
235
0
1
Order By: Relevance
“…Moreover, TMA-induced attraction required TAAR5 and PEA-induced aversion required TAAR4 (22,23). Together with the finding that individual fish and human TAARs recognize volatile amines aversive to those species (17,(24)(25)(26), these findings have suggested that the evolutionary conservation of the TAAR family may be linked to an ability to induce innate behaviors to volatile amines.…”
Section: Numerous Taar Ligands and Other Odorants Induce Innate Respomentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, TMA-induced attraction required TAAR5 and PEA-induced aversion required TAAR4 (22,23). Together with the finding that individual fish and human TAARs recognize volatile amines aversive to those species (17,(24)(25)(26), these findings have suggested that the evolutionary conservation of the TAAR family may be linked to an ability to induce innate behaviors to volatile amines.…”
Section: Numerous Taar Ligands and Other Odorants Induce Innate Respomentioning
confidence: 80%
“…At least some TAARs specifically recognize volatile amines, and two are required for behavioral attraction or avoidance to animal-derived amines (10,(21)(22)(23). In addition, one zebrafish TAAR ligand is aversive to fish (24), and one human TAAR detects an odorant aversive to humans as well as rotten fish (17,25,26). These observations have raised the possibility that the TAAR family may have an evolutionarily conserved ability to induce innate responses, particularly aversion.…”
mentioning
confidence: 99%
“…Ligands found thus far for TAARs are volatile amines, including several in mouse or predator urine (5,14,15). Ligands for a few mouse, fish, and human TAARs elicit aversive or attractive behaviors in their respective species, hinting at a conserved ability of TAARs to stimulate innate responses of potentially adaptive significance (5,6,14,16,17).…”
mentioning
confidence: 99%
“…We stimulated the larvae with the odorant cadaverine (Cad, 10-μM solution), a diamine generated by decarboxylation of the amino acid lysine during decomposition of flesh, which is known to evoke olfactory-related neural activity and avoidance responses in zebrafish larvae. 19,20 Figure 2 shows three image planes through the volumetrically reconstructed light field dataset [ Fig. 2(a)], as well as a top-down maximum intensity projection [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2(b')]. Clusters of activity could be found in the olfactory bulb (OB) and habenula (Hb), the latter considered to be involved in relaying odorevoked behavioral responses, 19,20 as well as in some neurons of the optic tectum (OT) [Figs. 2(b)-2(c)].…”
Section: Resultsmentioning
confidence: 99%